An Performance Study for Sectorised Antenna based Doppler Diversity in High-Speed Railway Communications - Cheng Tao; Jiahui Qiu; Houjin Chen; Liu Liu (Radioengineering, 2011)
The wireless channel of High-Speed Railway communication system is rapidly time-varying. The orthogonal frequency division multiplexing transmitting over this channel will be exposed to the intercarrier interference caused by large Doppler spread. The sectorised antenna can be employed for Doppler mitigation and obtaining Doppler diversity gain. In this paper the performance of this directional antenna is analyzed. The preferable partition scheme for the omnidirectional antenna and the optimal Doppler compensation frequency are addressed firstly. And the uncorrelated property of the signal received from the different sectorised antennas is demonstrated originally which can be utilized for Doppler diversity gain. Finally, it is proved by the simulation results that this architecture will allows us to achieve remarkable performance under high mobility conditions.